PELAKSANAAN PELELANGAN UMUM DENGAN SISTEM E-PROCUREMENT BERDASARKAN PERATURAN PRESIDEN REPUBLIK INDONESIA NOMOR 70 TAHUN 2012 - Pakarwati, Vintari; Mulyani, Endang; ., Syahrudin (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2014)
In the study, the study sample were contractors who have or are to follow the auction online at Kayong Northern District of West Kalimantan Province. Where this information research obtained from questionnaires and interviews directly to contractors in the district of North Kayong. From the research, it is known to follow the stages of E-Procurement (online auction) which starts from the opening LPSE site then register through the internet to be the SPSE (get a User Id and Password), the contractor can take part in the auction LPSE anywhere (one of which LPSE Kayong District North). To become a participant in the auction of the work package (with post qualification method) were tendered contractor registrations with the package, then download the document, and instructions to follow, prepare bid documents and upload documents and qualifications, as well as petitions (if any). While the results of the calculation method Likert Scale shows there are some constraints experienced contractors, among others, due to the difficult access to the internet network by 60%, the slow (loading) internet by 65,71%, non observant contractor in completing the qualification documents of 54,29% and the failure of the contractor at the time of uploading a document by 54,29% and 60% of power outages are caused by the relatively long period of time. Â  Â  Keywords: E-Procurement, Constraints, Stages